Retrospective analysis of exporting agricultural processing industry products - Yu. S. Lisachkina (Вестник университета)
The Russian exports of processed food products analysis since 2014 has revealed a stable growth in this area, corresponding to the general dynamics of domestic agricultural products sales in the world market. At the same time, the share of processed food products in the total volume of domestic exports from 2014 to 2021 increased from 1.7 to 3.1%, which is a favorable factor in reducing the mineral-raw materials orientation of Russia’s foreign trade. The increase in processed products exports contributes to the export-oriented nature of the domestic food industry, which grew from 6.5 to 11.6 % over the period. This is also due to the fact that import substitution programs development and competitive imports limitation after the counter-sanctions introduction in 2014-2015 had a favorable impact on the food industry and allowed to maintain and increase a number of export directions. Over the past few years, the key areas of sales in the global market have been the products of the oil and fat and sugar beet industries. Along with the sale of finished products, the food industry wastes export, which are raw materials for fodder production, is also considered important. With the overall positive dynamics of processed food sales, the only direction showing a decrease in exports is tobacco and tobacco products. The reduction in tobacco products exports is explained by the change in the transnational corporations policy who own the Russian cigarette business, which, in addition to the Russian market, until 2014 also partially filled the markets of the Commonwealth of Indepen dent States and Eastern Europe countries.